Determination of thermal and drying performances of the solar air dryer with solar tracking system: Apple drying test - Das, Mehmet; Akpinar, Ebru Kavak (Elsevier, 2020)
The present experimental study, the thermal performance of a solar air dryer with solar tracking system was investigated. Solar air collector (SAC) has been provided with solar tracking feature using a programmable logic control system that has not been used before. The SAC has been two-direction solar tracking feature with this system. The designed moving SAC was combined with a drying cabinet to obtain a solar air collector dryer (SACD). A fixed SACD, which is the same dimensions with the moving SACD, was designed to compare the performance of the moving SACD. In order to compare the thermal and the drying efficiencies of both systems, 14 mm thick apple slices were dried simultaneously. Depending on fan speed, in the moving and fixed SACD, the activation energy and effective moisture diffusivity values ranged from 0.062 x 10(-7) to 0.084 x 10(-7) m(2)/s and 33.2-40.01 kJ/mol and 0.031 x 10(-6) to 0.049 x 10(-6) m(2)/s and 16.4-22.9 kJ/mol, respectively. Convective heat transfer coefficient of apple slices showed changes in ranges 17.475-21.818 W/m(2)K in the moving SACD, and 13.215-20.846 W/m(2)K in the fixed SACD. The solar air collector thermal efficiency was calculated as 75.7% and 51.7% about in the moving and fixed SACD, respectively.
Keywords: Collector thermal efficiency; Convective heat transfer coefficient; Moisture diffusivity; Activation energy; Thin layer drying models